2018
DOI: 10.1007/s10461-018-2084-7
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of and Factors Associated with the Use of HIV Serosorting and Other Biomedical Prevention Strategies Among Men Who Have Sex with Men in a US Nationwide Survey

Abstract: PrEP and treatment-as-prevention (TasP) are biomedical strategies to reduce HIV transmission. Some men who have sex with men (MSM) are combining biomedical strategies with HIV serosorting-termed "biomed matching" when both partners are either on PrEP or TasP, or "biomed sorting" when one partner is using PrEP and the other TasP. Nevertheless, there is limited data on the extent of biomed matching/sorting in large geographically diverse samples. In 2016-2017, 5021 MSM from across the US were surveyed about thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 49 publications
3
28
0
5
Order By: Relevance
“…In line with our findings, all observed that, despite decreases, consistent condom use remained a dominant strategy in recent years, and the use of antiretroviral-based strategies was increasing [ 77 79 ]. Regarding biomedical seroadaptive behaviours, Grov et al [ 80 ] also considered these and witnessed PrEP and viral load sorting taking place amongst GBM in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…In line with our findings, all observed that, despite decreases, consistent condom use remained a dominant strategy in recent years, and the use of antiretroviral-based strategies was increasing [ 77 79 ]. Regarding biomedical seroadaptive behaviours, Grov et al [ 80 ] also considered these and witnessed PrEP and viral load sorting taking place amongst GBM in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 Other benefits of PrEP use have been documented from GBMSM on PrEP, including increasing feelings of intimacy with partners, improving one's sex life, and enhancing feelings of agency over sexual health. 33,34,36,37 Our own work (S.G.) indicates that PrEP use can have ancillary benefits of NEXT-WAVE PREP IMPLEMENTATION 255…”
Section: Focusing On Hiv Risk Perception Is Not a Sustainable Strategmentioning
confidence: 99%
“… 2 5 We found that among MSM enrolled in a cross-sectional survey in Montreal, Canada, those on PrEP reported a higher proportion of partners on PrEP among their HIV-negative partners than would be expected by chance alone (50.6% vs. 28.5%)—a pattern we referred to as “PrEP-matching.” 2 Similarly, using data from a nationwide survey of MSM in the United States, Grov et al found that MSM who used PrEP reported a larger proportion of partners on PrEP among their casual male partners, compared with HIV-negative MSM who did not use PrEP (41% vs. 22%)—a pattern referred to as a form of “biomed-matching” by the authors. 3 The term “biomed-matching” was originally introduced by Newcomb et al 4 to describe an emerging risk reduction strategy used by MSM in the era of biomedical HIV prevention, wherein both individuals in the partnership use PrEP or have undetectable viral load to engage in condomless sex. Indeed, Prescott et al, 5 found that among a sample of MSM who use alcohol in San Francisco, United States, approximately half of the sexual partnerships among MSM using PrEP were concordant in their use of biomedical prevention, and their concordant use of PrEP was associated with greater engagement in condomless anal sex.…”
mentioning
confidence: 99%